Dinamika Stereotipe Digital di Media Sosial dalam Perspektif Komunikasi Islam: Analisis Kognitif, Struktural, dan Normatif - Desnas Atanti; Khusnul Khatimah (Kartika: Jurnal Studi Keislaman, 2026)
This study examines the transformation of stereotype formation and dissemination in the digital era. The research addresses a critical gap, namely the absence of an integrative framework that combines individual psychological processes, media algorithm mechanisms, and Islamic communication values in understanding digital stereotypes. This study aims to analyze the layers shaping digital stereotypes, identify their emerging characteristics, and formulate the role of Islamic communication in reducing stereotypes. The research employs a library research approach by analyzing recent scholarly literature using thematic content analysis. The findings reveal that digital stereotypes are constructed through three interconnected layers: cognitive (social categorization), structural (media algorithms), and normative-ethical (Islamic communication values). Furthermore, four defining characteristics of digital stereotypes are identified: viral dissemination, algorithmic reinforcement, moral framing, and resistance to correction. The novelty of this study lies in the development of a three-level integrative model that combines cognitive literacy, structural awareness of media systems, and the internalization of Islamic communication ethics, including tabayyun (verification), husnuzan (positive presumption), and 'adl (justice). The study concludes that Islamic communication plays a strategic role as an ethical foundation for fostering a more just and civilized digital public sphere. These findings imply the need to strengthen digital literacy grounded in Islamic communication ethics within plural societies.